1997
DOI: 10.1002/elps.1150181110
|View full text |Cite
|
Sign up to set email alerts
|

Further genetic heterogeneity in acatalasemia

Abstract: A T-deletion at position 10 of exon 4 for catalase gene was reported as a novel mutation, causing a new genetic type of acatalasemia in Japan. This mutation, destroying a Hinf1 recognition site, was searched for in Hungarian acatalasemic (2) and hypocatalasemic (22) patients and in controls (27) by Hinf1 digestion and sequence analyses of a 203 bp polymerase chain reaction (PCR) product containing the entire exon 4. The Hinf1 polymorphism did not reveal any difference between controls and hypocatalasemic as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In contrast, none of the 66 normocatalasemic family members suffered from diabetes mellitus [13,14]. Genetic analysis of these families showed that the known types of Japanese acatalasemia (2) were not found in the Hungarian families [15,16].…”
Section: Introductionmentioning
confidence: 73%
“…In contrast, none of the 66 normocatalasemic family members suffered from diabetes mellitus [13,14]. Genetic analysis of these families showed that the known types of Japanese acatalasemia (2) were not found in the Hungarian families [15,16].…”
Section: Introductionmentioning
confidence: 73%
“…We have reported on two acatalasemic sisters in the first Hungarian acatalasemic family [9] and nine hypocatalasemic families [10] with 37 hypocatalasemics including the biochemical markers of lipid and carbohydrate metabolism in acatalasemia and hypocatalasemia [11]. In Hungarian acatalasemic and hypocatalasemic patients, we could not detect the mutations responsible for the defect catalase synthesis in Japanese patients [12,13]. For the acatalasemic and three hypocatalasemic families, we found a GA insertion at position 138 of exon 2.…”
mentioning
confidence: 82%
“…In step two, compound I oxidizes a second peroxide molecule to molecular oxygen and releases the ferryl oxygen species as water. Several catalase crystal structures have been determined, aiding our understanding of reactive oxygen control by defining the reaction and inhibition mechanisms (Goth, 1997). These studies include the definition of the chemistry of the human catalase, through structures of the resting-state enzyme and complexes of a catalase bound to cyanide and 3AT inhibitors (Putnam et al, 2000).…”
Section: Hydrogen Peroxide Removal By Catalasementioning
confidence: 99%